Benelux as a Successful Model for Regional Cooperation - Applicability for Bulgaria and SEE - Valtchev, Bojko (Research Papers, 2018)
The current research aims at exploring the experience of the Benelux countries in regional cooperation and outlining the factors that made Benelux the most successful regional format. The research is based on historic and legal analysis. The main conclusion points out that the success of Benelux is mainly due to the similar level of development, the small number of participating countries, the high level of trust and the political will for cooperation as well as a suitable institutional framework that channels the political will into concrete initiatives and projects.
Keywords: Sustainable development; Benelux; Annual plan; 4-year framework; Regional cooperation